Impact of Mycorrhiza Application and Variety on the Growth and Productivity of Chili Pepper (Capsicum frutescens L.) - Mizan Maulana; Rika Yusli Harta; Zaitun Ritaqwin; Sarah Nadia (Jurnal Ilmu Pertanian Indonesia, 2026)
This study aimed to assess the influence of mycorrhiza and variety on the growth and yield of chili pepper plants, along with the interaction between these two factors. The research employed a 3 × 4 Factorial Randomized Block Design (RAK), leading to 12 treatment combinations. Each combination was conducted three times, resulting in a total of 36 experimental units. The initial factor was the mycorrhiza amount, which included control, 10, 20, and 30 g for each plant. The second factor was chili variety, which included Panca, Rajo, and Ramos. The monitored parameters included increases in plant height, stem diameter, leaf count, flower count, fruit count per plant, fruit weight per plant, fresh stem weight, fresh root weight, root length, and percentage of roots infected with mycorrhiza. Inoculation with mycorrhiza significantly influenced plant height at 45 days after transplanting (DAT), but did not have a meaningful effect on plant height at 15 and 30 DAT, stem diameter at 15 and 30 DAT, number of leaves, number of flowers, number of fruits per plant, fresh stem weight, fresh root weight, and root length. The effect of varieties on the parameters observed showed no significant effect on plant height, stem diameter, number of leaves, number of flowers, number of fruits per plant, fresh weight of the stem, fresh weight of the roots, and root length. Keywords: root length, mycorrhiza, varieties